1988
DOI: 10.2165/00003495-198836040-00003
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin

Abstract: Lovastatin is the first of a new class of cholesterol lowering drugs that competitively inhibit HMG-CoA reductase. This new drug decreases cholesterol synthesis and apolipoprotein B concentrations, and increases LDL receptor activity without adverse effects on other products in the cholesterol pathway. In patients with heterozygous familial or polygenic (non-familial) hypercholesterolaemia, oral lovastatin 20 to 40 mg twice daily reduces plasma total cholesterol and LDL-cholesterol concentrations by 25 to 40% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Lovastatin reduces LDL cholesterol concentrations by 25-40% in hypercholesterolemic patients [151][152][153] and decreases plasma TG and VLDL levels in hypertriglyceridemic patients [102,154]. Weintraub et al found that lovastatin exerts a better TG-lowering effect in patients with mildly elevated TG levels (160-240 mg/dl; 1.8 -2.7 mmol/l) rather than at lower levels (<160 mg/dl; 1.8 mmol/) [110].…”
Section: Lovastatinmentioning
confidence: 99%
“…Lovastatin reduces LDL cholesterol concentrations by 25-40% in hypercholesterolemic patients [151][152][153] and decreases plasma TG and VLDL levels in hypertriglyceridemic patients [102,154]. Weintraub et al found that lovastatin exerts a better TG-lowering effect in patients with mildly elevated TG levels (160-240 mg/dl; 1.8 -2.7 mmol/l) rather than at lower levels (<160 mg/dl; 1.8 mmol/) [110].…”
Section: Lovastatinmentioning
confidence: 99%
“…Simvastatin and pravastatin are chemical modifications of lovastatin originally derived from a fungal source [3,4,5]. Both lovastatin and simvastatin, administered as pro-drug or lactone forms, differ from the other statins administered as the active or beta-hydroxyacid ( Fig.…”
Section: Chemical Nature Of Statinsmentioning
confidence: 99%
“…They cause a reversible competitive inhibition of the microsomal hydroxymethyl-glutaryl coenzyme A (HMG-CoA) reductase; thus, they prevent the reduction of HMG-CoA to mevalonic acid and the formation of cholesterol [2]. The major Monascus metabolite is monacolin K, which is structurally identical to lovastatin, the first statin drug introduced into the market [3,4]. The red yeast rice products that are currently marketed as food supplements differ from the traditional red yeast rice that is sold in Chinese groceries.…”
Section: Introductionmentioning
confidence: 99%